2011
DOI: 10.3109/09540261.2010.549117
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry and primary care integration: Challenges and opportunities

Abstract: Health systems across the world remain significantly fragmented, affecting access, quality and costs of the care delivered. Strengthening health systems is a global health challenge for all countries: low, middle and high income. According to the World Health Organization the key components of a well functioning health system, namely, leadership and governance, health information systems, health financing, human resources for health, essential medical products and technologies, and services delivery are sine q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Fortunately, a number of studies have shown that improving the provision of mental health services in primary care practices is both effective (Bao et al 2013;Hedrick et al 2003;Katon et al 2002;Kessler and Stafford 2008;Sorel and Everett 2011) and efficient (Katon et al 2002;Kessler and Stafford 2008;Rost et al 2005;Sorel and Everett 2011). Not only are these approaches effective for mental health problems, they have also been shown to be efficacious components of the treatment of medical conditions (Allen et al 2002;Dickinson and Miller 2010;Kessler and Stafford 2008;Raine et al 2002).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Fortunately, a number of studies have shown that improving the provision of mental health services in primary care practices is both effective (Bao et al 2013;Hedrick et al 2003;Katon et al 2002;Kessler and Stafford 2008;Sorel and Everett 2011) and efficient (Katon et al 2002;Kessler and Stafford 2008;Rost et al 2005;Sorel and Everett 2011). Not only are these approaches effective for mental health problems, they have also been shown to be efficacious components of the treatment of medical conditions (Allen et al 2002;Dickinson and Miller 2010;Kessler and Stafford 2008;Raine et al 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Information on the preferences of their patients is needed. Patient preferences for mental health screening strongly affect whether they are identified within the primary care context as having a need for these services (Arcury and Quandt 2007;Caldwell et al 2008;Renzaho et al 2013), and patients' preferences determine whether they get the care they need-both in terms of access and adherence (Arcury and Quandt 2007;Caldwell et al 2008;Kessler and Stafford 2008;Scholle et al 2003;Sorel and Everett 2011;Watkins et al 2001;Williams et al 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The 2010 Patient Affordable Care Act (ACA) embraces patient‐centred medical care as a means not only to improve health outcomes, but also to address inequalities in care among ethnic, minority and low‐income populations. Primary care settings are the nucleus of the patient‐centred approach and are becoming widely recognized as a critical and rapidly growing venue for the delivery of mental health services . For example, in caring for patients with chronic disease, primary care physicians often encounter concurrent depression and anxiety that, left untreated, will adversely impact the course of the chronic illness .…”
mentioning
confidence: 99%
“…Avanços para implementar o princípio da integralidade estão ocorrendo, através da elaboração de programas voltados para mulheres, crianças, adolescentes, idosos, portadores de doenças infecciosas, portadores de doenças mentais, dentre outros, assim como iniciativas para estruturação da rede em ordem crescente de complexidade (BRASIL, 2000). Devido à relevância do assunto, muitos estudiosos têm pesquisado o tema (STARFIELD, 2002;KNOWLES, 2009;SCHUFFMAN;DRUSS;PARKS, 2009;KIRCHNER et al, 2010;HANRAHAN;DELANEY;MERWIN, 2010;KATHOL et al, 2010;POMERANTZ;SAYERS;PETERSEN et al, 2011;SOREL;EVERETT, 2011;STEMBERG;HOMER, 2011;VAN DER FELTZ-CORNELIS, 2011;BOSTWICK;RACKLEY, 2012;CROFT et al, 2013;ERICKSON, 2012 CHERCHIGLIA, 2008;CONSOLI;HIRDES;COSTA, 2009;COIMBRA et al,2011).…”
Section: Apsunclassified